Yahoo Web Search

  1. Sort by

  1. * LHS * Note that csc(x) = 1/sin(x) sin(x)/(1/sin(x) - 1) + sin...(x) ==> 2tan²(x) You are correct that LHS ≠ RHS! See link for proof: http://www.wolframalpha.com/input...

    1 Answers · Education & Reference · 08/04/2011

  2. LHS = sinx - sinx cos² x = sinx [1 - cos² x] = sinx * sin² x...

    1 Answers · Education & Reference · 09/12/2012

  3. 1. LHS . . . . RHS cos(6x) = 2cos²(3x) - 1 * * * Rewrite cos(6x...

    1 Answers · Education & Reference · 22/03/2011

  4. LHS = [1/(secx - 1)] * [1/(secx + 1)] = 1 / (sec² x - 1) ... [using the difference...so 1 - cos² x = sin² x] = cot² x = RHS LHS = [(tanx - cotx) / (tanx + cotx)] + 1 = [{(sinx/cosx) - (cosx / sinx)} / {(sinx / cosx) + (cosx...

    1 Answers · Education & Reference · 13/12/2011

  5. * LHS * Since LCD is sin(x)cos(x)... (sin(x) - cos(x))/sin(x...

    1 Answers · Education & Reference · 10/07/2011

  6. LHS = sinx secx = sinx (1/cosx) = sinx / cosx = tanx = RHS so sinx secx = tanx...cos(2x)] and substituting 2x for x in the identities like this: LHS = cos^2(2x) - sin^2(2x) = (1/2) [cos(4x) + 1] - (1/2)[1 - cos(4x)] = (1/2)cos(4x...

    1 Answers · Education & Reference · 30/03/2009

  7. LHS means the 'left hand side' and is 'a - (c - (a/2))'...right hand side' and is '(3a - c)/2'. We need to find out if LHS = RHS, so: LHS = a - ((c - a)/2) = a - c/2 + a/2 = 2a/2...

    1 Answers · Education & Reference · 22/08/2012

  8. LHS = sin(7π/6 + x) - cos(2π/3 + x) = sin (7π/6) cosx + cos (7π/6) sinx - [cos (2π...

    1 Answers · Education & Reference · 23/10/2012

  9. LHS = sec (2x) - tan (2x) = [1 / cos (2x)] - [sin (2x) / cos (2x)] = [1 - sin (2x)] / cos (2x...

    1 Answers · Education & Reference · 03/12/2011

  10. 1) LHS = cot² x + csc² x = (cos² x / sin² x) + (1... x / sin² x) = 2csc² x - 1 = RHS 2) LHS = csc² u - cos u sec u = (1 / sin² u) - cos u * (1 / cos u...

    2 Answers · Education & Reference · 30/04/2012

  1. Try asking your question on Yahoo Answers